Eating disorders and carbohydrate metabolism interrelations - Niedobylski, Sylwiusz; Skarbek, Małgorzata; Tomasik, Justyna; Zaręba, Bartłomiej; Zawadzka, Żaneta; Próchnicki, Michał; Rudzki, Grzegorz (Current Problems of Psychiatry, 2022)
Introduction. Eating disorders are characterised by persistent disturbances in eating behavior, resulting in severe carbohydrate homeostasis changes. The aim of the study is to review mutual correlations between eating disorders, with emphasis on anorexia nervosa, and carbohydrate metabolism, including glycemia and the levels of relevant hormones. Material and methods. A priori general inclusion criteria were established and included patients with eating disorders or with glucose metabolism disorders. A MEDLINE database review was carried out. Relevant articles have been extracted and approved by supervisor. Results. 40 studies got included in the review. Patients with active anorexia nervosa display low levels of fasting and postprandial glucose, decreased lipid metabolism, and decreased pancreatic endocrine activity. Insulin levels remain changed even after patient’s re-nourishment – insulin response tends to be delayed and decreased compared to patients without anorexia history. Eating disorders are associated with poorer glycemic control and a higher percentage of diabetic complications in patients with pre-existing diabetes – mostly type I. There are also reports of higher carbohydrate metabolism disturbances among patients with eating disorders. Conclusions. Carbohydrate metabolism disorders and eating disorders are clearly interrelated, although data on the nature of these relationships are still lacking. Treatment of eating disorders is not possible without normalizing eating patterns, thus also carbohydrate metabolism. However, it is not usual to monitor the mental state in terms of eating disorders potential development in patients during the treatment of carbohydrate disorders. According to existing data, this approach should be changed due to the risk of anorexia nervosa and other eating disorders in this group.